2008
DOI: 10.1530/eje-08-0393
|View full text |Cite
|
Sign up to set email alerts
|

Hypochondroplasia and acanthosis nigricans: a new syndrome due to the p.Lys650Thr mutation in the fibroblast growth factor receptor 3 gene?

Abstract: Background: Hypochondroplasia (HCH) is a skeletal dysplasia inherited in an autosomal dominant manner due, in most cases, to mutations in the fibroblast growth factor receptor 3 (FGFR3). Acanthosis nigricans (AN) is a velvety and papillomatous pigmented hyperkeratosis of the skin, which has been recognized in some genetic disorders more severe than HCH involving the FGFR3 gene. Objective and design: After initial study of the proband, who had been consulted for short stature and who also presented AN, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 31 publications
0
38
0
1
Order By: Relevance
“…The Lys650Asn and Lys650Gln mutations lead to hypochondroplasia (HCH), a mild form of dwarfism (Bellus et al, 1995; Bellus et al, 2000). The Lys650Thr mutation causes an even milder form of HCH (Berk et al, 2007; Castro-Feijoo et al, 2008). In vitro autophosphorylation assays have shown that these mutations confer different degrees of ligand-independent activation on FGFR kinase, and that the degree of aberrant activation correlates with the clinical severity of the dwarfism syndromes caused by the mutations (Bellus et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The Lys650Asn and Lys650Gln mutations lead to hypochondroplasia (HCH), a mild form of dwarfism (Bellus et al, 1995; Bellus et al, 2000). The Lys650Thr mutation causes an even milder form of HCH (Berk et al, 2007; Castro-Feijoo et al, 2008). In vitro autophosphorylation assays have shown that these mutations confer different degrees of ligand-independent activation on FGFR kinase, and that the degree of aberrant activation correlates with the clinical severity of the dwarfism syndromes caused by the mutations (Bellus et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, familial AN without any obvious skeletal abnormality has been reported in association with a mutation in FGFR3 (p.K650T) (3). Interestingly, the same mutation has also been found in a family with hypochondroplasia (HCH) and extensive AN (4). There have been only two reported cases of AN in patients with ACH without SADDAN (5,6) and one in a patient with mild osteochondrodysplasia (p.K650Q) (7).…”
mentioning
confidence: 96%
“…Codon 540 in exon 13 is a major hotspot (7). The other mutations of this gene account for fewer than 2% of HCP patients (8). However, familial cases who were not linked to FGFR3 have been reported that support a genetically heterogeneous condition (9,10).…”
Section: Discussionmentioning
confidence: 99%